PEER COMMUNICATIONS INFLUENCE ON PURCHASE INTENTION OF BEAUTY PRODUCTS - Wong, Wen Chee; Syriac, Nellikunnel (INTI International University, 2023)
One of the fast-growing industries identified is beauty-care industry. Different factors are influencing beauty enthusiasts on purchasing intention. Nowadays, peer communication has become important in marketing process as it is a multi-dimensional two-way activity. However, there are limited research conducted in the context of beauty products. Therefore, the findings of this research are useful to tighten the gap of knowledge to academe, and to be a reference for marketing plan in beauty industry. Questionnaire is distributed randomly and is done with various analysis tools in SPSS, such as Correlation Analysis, Reliability Analysis, Multiple Regression Analysis. From the findings of this research, we found that social media dependency and public-organization engagement have significantly influenced the purchase intention of beauty products, while tie-strength has not significantly influenced the purchase intention. Therefore, brands should have a consistent image across social media platforms and influence the followers with helpful information and entertaining videos. Public-organization engagement should be improved and maintained to increase the purchase intention among consumers